2018
DOI: 10.1371/journal.pone.0205448
|View full text |Cite
|
Sign up to set email alerts
|

NAM gene allelic composition and its relation to grain-filling duration and nitrogen utilisation efficiency of Australian wheat

Abstract: Optimising nitrogen fertiliser management in combination with using high nitrogen efficient wheat cultivars is the most effective strategy to maximise productivity in a cost-efficient manner. The present study was designed to investigate the associations between nitrogen utilisation efficiency (NUtE) and the allelic composition of the NAM genes in Australian wheat cultivars. As results, the non-functional NAM-B1 allele was more responsive to the nitrogen levels and increased NUtE significantly, leading to a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
(59 reference statements)
2
19
0
1
Order By: Relevance
“…In Mace, GY and GPC were less affected by N stress compared to those in Spitfire and Volcani in glasshouse conditions, although under high N conditions, the GPC of Spitfire and Volcani was higher than that of Mace. In agreement with the previous study (Alhabbar et al, 2018b), this study further confirms that Mace is more tolerant of N stress. It was reported that the GY in maize was decreased by 38% with the change in N treatment from high to low (Gallais and Hirel, 2004), which can be associated with the interrupted synthesis of chlorophyll and photosynthesis performance (McCullough et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In Mace, GY and GPC were less affected by N stress compared to those in Spitfire and Volcani in glasshouse conditions, although under high N conditions, the GPC of Spitfire and Volcani was higher than that of Mace. In agreement with the previous study (Alhabbar et al, 2018b), this study further confirms that Mace is more tolerant of N stress. It was reported that the GY in maize was decreased by 38% with the change in N treatment from high to low (Gallais and Hirel, 2004), which can be associated with the interrupted synthesis of chlorophyll and photosynthesis performance (McCullough et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…This study investigated three Australian bread wheat varieties, Mace, Spitfire, and Volcani, which are known to have high, medium, and low NUEs, respectively (Alhabbar et al, 2018b). Since gene expression in plants is controlled in a temporal and tissue-specific manner (Koltunow et al, 1990;Maizel and Weigel, 2004) and the N demand is subject to plant developmental stages, the current study used different tissues at different growth stages to unravel the broad picture of transcriptome profile with the objectives of identifying novel genes that are differentially expressed under long-term N stress compared to high N treatment, and by characterizing the underlying physiological and molecular mechanisms of tolerance to N stress.…”
Section: Introductionmentioning
confidence: 99%
“…Asterisks and bold coloured lettering indicate known variants, including AA substitutions identified for 1189a in orange (G159E, NAM-Al), 2316b in blue (TlSl, NAM-D1), natural NAM-Al variants in pink (Cormier et al , 2015), EMS-induced NAM-Al missense mutations in yellow (Harrington et al , 2019a), EMS-induced knockout mutations in green (Avni et al , 2014) and red (Pearce et al , 2014). In Triticum aestivum NAM-Bl is largely non-functional due to a +1 bp frameshift mutation, or complete deletion (Uauy et al , 2006a; Hagenblad et al , 2012; Alhabbar et al , 2018a; Alhabbar et al , 2018b). Accession numbers are, NAM-Al, TraesCS6A02G108300.1; NAM-Bl, UniProtKB/Swiss-Prot: A0SPJ4.1 (Triticum turgidum ssp.…”
Section: Resultsmentioning
confidence: 99%
“…while the modern wheat cultivars carry the nonfunctional allele 34 . The expression analysis of NAM alleles showed high expression of NAM-A1, -B1 and -D1 in the stamens and spikelets, while NAM-B1 is also expressed in the flag leaf 35 . This can explain the spikelet/floret sterility in the modern cultivars that are carrying alleles NAM-A1 and NAM-D1, and demonstrates the role of NAM-B1 allele in spikelet development in our collection, because of improving nitrogen use efficiency and grain yield.…”
Section: Discussionmentioning
confidence: 98%